Incorporating working volume and projected area in design criteria for automotive SLA suspension - Silveira, Marcos [UNESP]; Fernandes, Júlio César de Moraes [UNESP] (Springer Nature, 2022)
In this paper, we introduce the concept of working volume of an automotive suspension system as a measure of the space occupied by it, and exemplify its use in design criteria for more compact suspension systems. This can aid in satisfying the increasing constraints imposed by electric vehicles, which need more space for batteries and in-wheel motors, while also accounting for kinematical performance measures. The design criteria are first illustrated in a planar model via the concept of projected working area, and then used in a spatial model as the working volume. A large amplitude model of a SLA double wishbone suspension is used which includes geometrical nonlinear terms. The design criteria are first illustrated in a planar model via the concept of projected working area, and then used in a spatial model as the working volume. Planar and spatial analyses show that a simpler model can give valuable insight into the camber and track behaviour of the suspension system, while also serving as good predictor of the working volume of the spatial model. With the procedure presented in the manuscript, a designer is able to directly relate a reduction in area with resulting camber gain and track variation, or any other kinematic metric of choice, which can greatly simplify the process of a preliminary design. Although the criteria are defined based on a double wishbone geometry, they can be used in other geometries.
Keywords: Design criteria; Suspension kinematics; Working volume